Pyogenic Sacroiliitis in Children: Two Case Reports - L. Ghedira Besbes; S. Haddad; A. Abid; Ch. Ben Meriem; M. N. Gueddiche (Case Reports in Medicine)
Pyogenic sacroiliitis is rare and accounts for approximately 1-2% of osteoarticular infections in children. Considerable delay between presentation and diagnosis is recognized. Two cases of pyogenic sacroiliitis are described. The first case is a 28-month-old girl presented with acute onset of fever, pain in the left hip, and limpness. Computed tomography (CT), bone scans, and magnetic resonance imaging (MRI) of the pelvis showed characteristic findings of infectious sacroiliitis, and blood cultures were negatives. The second case is a 13-year-old girl presented with acute onset of fever, pain in the right hip, and buttock, with inability to walk. The diagnosis of pyogenic sacroiliitis was confirmed by bone scans, and CT of the pelvis and blood cultures have identified Proteus mirabilis. The two children recovered fully after 6 weeks of antimicrobial therapy. Pyogenic sacroiliitis is an uncommon disease in children. The key to successful management is early diagnosis in which CT, bone scans, and MRI findings play a crucial role. If the diagnosis is established promptly, most patients can be managed successfully with antimicrobial therapy.